AN ASSESSMENT OF INFRASTRUCTURE FACILITIES IN RURAL AREA: A STUDY IN KHARKHODA BLOCK OF SONIPAT DISTRICT, HARYANA - Preeti; Dr. Mehtab Singh (Universal Research Reports, 2023)
The rural lifestyle has undergone significant changes due to the lack of facilities, amenities, and social equality, leading to a notable migration from rural to urban areas. This migration has resulted in population growth, socio-economic fluctuations, and environmental pollution in urban centres, while rural areas are left deserted with declining economic opportunities. Infrastructure development plays an important role in fostering both economic growth and poverty reduction. Despite government initiatives, the desired goals for rural infrastructure development have not been achieved. The paper studied the status of infrastructural facilities in Kharkhoda block of Sonipat district, Haryana and analysed the magnitude of the deficiency of these infrastructural facilities. Using data based on the primary survey the research concludes that all the services i.e. banks, parks, playgrounds, community centres and police stations are deficient in this area.